The virgin suicides - Eugenides, Jeffrey (New York : Picador, 2009)
The narrator and his friends try to piece together facts and gossip about a tragic suicide that happened twenty years earlier.
Wilson's Fiction, January 1996
Library Journal Starred, August 2007
Publisher's Weekly, October 2007
Booklist, February 2007
New York Times, March 2007
Kirkus Review, July 2007
Keywords: Teenagers -- United States -- Suicidal behavior -- Fiction; Suburban life -- United States -- Fiction; Teenage girls -- United States -- Fiction; Sisters -- United States -- Fiction; Memory -- Fiction; Teenagers -- United States -- Fiction; Suicide -- Fiction; Suburban life -- United States -- Fiction; Girls -- United States -- Fiction; Sisters -- Fiction; Memory -- Fiction; Mystery fiction; Mystery fiction